Effects of preheat treatments on the composition, rheological properties, and physical stability of soybean oil bodies. Issue 10 (7th September 2020) - Fu, Liwei; He, Zhiyong; Zeng, Maomao; Qin, Fang; Chen, Jie
Abstract : Abstract: This study investigated the effects of preheat treatments on the composition, rheological properties, and the physical stability of soybean oil bodies and examined the stability of coffee containing those oil bodies. Three preheat treatment methods were compared, including heating (at 65, 75, and 85 °C for 30 min) of raw soymilk, high‐pressure steam heating (at 110, 120, and 130 °C for 10 s, ultra high temperature [UHT] treated) of dry soybeans, and milling of soaked soybeans in boiling water. Three UHT samples showed the highest oil body yields (13.59 to 13.87%) and protein yield (2.47 to 3.03%), while oil content in extracts was the lowest (30.97 to 46.25%). Soymilk heated at 65 or 75 °C for 30 min showed high oil body extraction yields (13.38 and 11.46%) and the highest oil extraction yields (6.38 to 8.38%) among all the samples. Three UHT samples had a higher average particle size and higher apparent viscosity compared with those of all the other samples. The results from sodium dodecyl sulfate‐polyacrylamide gel electrophoresis (SDS‐PAGE) and particle size distribution suggested heat treatment at 65 to 85 °C just lead to the partially denaturation and unfolding of storage protein instead of severe aggregation, while UHT (samples 5, 6, and 7) could lead to large amount soluble aggregates within oleosins and storage proteins via disulfide bonds. The diluted emulsion with 12% fat content remained stable during a 15‐day storage period at 4 °C. The coffee stability of the diluted oil body emulsion indicated high oleosins and low storage protein content in the oil body was a benefit for the coffee stability. Practical Application: Soybean oil bodies are natural sources of pre‐emulsified oil derived from soybean and can be dispersed in an aqueous medium to form a stable emulsion system. This study provides the foundation for the preparation and application of soybean oil bodies with differing emulsion stabilities and extraction yields in the food industry.